2020
DOI: 10.1021/acs.est.0c04421
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation, Biotransformation, and Multicompartmental Toxicokinetic Model of Antibiotics in Sea Cucumber (Apostichopus japonicus)

Abstract: Extensive application of antibiotics leads to their ubiquitous occurrence in coastal aquatic environments. However, it remains largely unknown whether antibiotics can be bioaccumulated and biotransformed in major mariculture organisms such as sea cucumbers and toxicokinetic models for Echinodermata are lacking. In this study, laboratory exposure experiments on juvenile sea cucumber (Apostichopus japonicus) were performed for seven antibiotics (sulfadiazine, sulfamethoxazole, trimethoprim, enrofloxacin, ofloxac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 86 publications
0
20
0
3
Order By: Relevance
“…In the depuration phase, C UV-P,j decreased quickly in all of the tissues and dropped below LODs in the gills, intestines, livers, ovaries, and muscles between days 32 and 34. Previous studies also observed rapid uptake and depuration of chemicals with low log K OW (e.g., sulfonamides 68 ) in aquatic organisms, while those with high log K OW (e.g., dioxins 69 ) were the opposite.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…In the depuration phase, C UV-P,j decreased quickly in all of the tissues and dropped below LODs in the gills, intestines, livers, ovaries, and muscles between days 32 and 34. Previous studies also observed rapid uptake and depuration of chemicals with low log K OW (e.g., sulfonamides 68 ) in aquatic organisms, while those with high log K OW (e.g., dioxins 69 ) were the opposite.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…Given parameter values in Table 4, we performed simulations over time for the six antibiotics and the four internal organs. As shown in Figure 6, we reproduced the same median curves as those of 46 in Figure S10 of their supplementary information.…”
Section: Table 4 Parameter Values For the Five-compartment Physiologi...mentioning
confidence: 92%
“…Two case studies concern the species Gammarus fossarum exposed to cadmium (Cd). 27, 45 The third one concerns Apostichopus japonicus sea cucumber exposed to six different antibiotics; 46 the fourth one concerns species Danio rerio exposed to arsenic (As). 47 Gestin and colleagues 27,45 used several one-compartment PBK models compared with one four-compartment PBK model to gain knowledge on the accumulation and fate dynamic of Cd in and between gammarids' organs.…”
Section: Case Studies In Ecotoxicologymentioning
confidence: 99%
See 2 more Smart Citations